Neuroprogenitor Cells From Patients With TBCK Encephalopathy Suggest Deregulation of Early Secretory Vesicle Transport - Moreira, Danielle de Paula; Suzuki, Angela May; Silva, André Luiz Teles e; Varella-Branco, Elisa; Meneghetti, Maria Cecília Zorél; Kobayashi, Gerson Shigeru; Fogo, Mariana; Ferrari, Merari de Fátima Ramires; Cardoso, Rafaela Regina; Lourenço, Naila Cristina Vilaça; Griesi-Oliveira, Karina; Zachi, Elaine Cristina; et al. (Frontiers in Cellular Neuroscience, 2022)
Biallelic pathogenic variants in TBCK cause encephaloneuropathy, infantile hypotonia with psychomotor retardation, and characteristic facies 3 (IHPRF3). The molecular mechanisms underlying its neuronal phenotype are largely unexplored. In this study, we reported two sisters, who harbored biallelic variants in TBCK and met diagnostic criteria for IHPRF3. We provided evidence that TBCK may play an important role in the early secretory pathway in neuroprogenitor cells (iNPC) differentiated from induced pluripotent stem cells (iPSC). Lack of functional TBCK protein in iNPC is associated with impaired endoplasmic reticulum-to-Golgi vesicle transport and autophagosome biogenesis, as well as altered cell cycle progression and severe impairment in the capacity of migration. Alteration in these processes, which are crucial for neurogenesis, neuronal migration, and cytoarchitecture organization, may represent an important causative mechanism of both neurodevelopmental and neurodegenerative phenotypes observed in IHPRF3. Whether reduced mechanistic target of rapamycin (mTOR) signaling is secondary to impaired TBCK function over other secretory transport regulators still needs further investigation.